2020
DOI: 10.17306/j.afs.0685
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical, texture hardness and sensorial properties of ultrafiltrated low-fat cheese containinggalactomannan and novagel gum

Abstract: Background. Today's demand for low-fat dairy products, especially cheeses with favorable qualitative properties such as high-fat cheese, has increased. The main goals of this research are to optimize the textural hardness properties of ultrafiltrated, low-fat cheese (7-9%), to investigate the possibility of its production with various concentrations of galactomannan and novagel (0.1-0.5%), and to assess the physicochemical, textural hardness and sensorial properties of the produced low-fat cheese in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As could be seen, from day 0 to day 2, the hardness of Mongolian cheese increased in both groups, which was related to the high water loss. The interaction between proteins increased, and the protein shrank, the internal water was discharged, the surface became dry, resulting in an increase of the hardness (Sharafi et al, 2020). As ripening progressed, hardness decreased and all cheeses softened at the end of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…As could be seen, from day 0 to day 2, the hardness of Mongolian cheese increased in both groups, which was related to the high water loss. The interaction between proteins increased, and the protein shrank, the internal water was discharged, the surface became dry, resulting in an increase of the hardness (Sharafi et al, 2020). As ripening progressed, hardness decreased and all cheeses softened at the end of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…The ash contents in the control samples increased significantly (P<0.05) from (1.22±0.005 and 1.69±0.02) to (1.81±0.03 and 2.38±0.06) after subjecting to sanitating solution. Sharafi et al [23] indicated that the direct effects of galactomannan and novagel gum can increased the ash content in the lowfat cheese. These results were disagreed with Murtaza et al [24] who reported that there was no effect in the ash contents after addition of Gum to the low-fat cheddar cheese.…”
Section: Resultsmentioning
confidence: 99%